Antimicrobial Resistance Of Escherichia Coli Isolates In Pig Farm Workers, Normal And Diarrhoeic Pigs - Choo, Raymond Pow Yoon (1991)

(untitled)
The enumeration of coliforms in faeces can be per formed by both the spread plate method or Most Probable Number ( MPN ) techniques , although MPN total coliform counts are significantly higher ( P<0.05 ) . In so lid agar media enumeration , MacConkey , Desoxycholate , Eosin-Methylene Blue and ENDO agars are suitable media for the enumeration of coliforms . The correlation coefficients of counts among media and technique is high . The mean colony forming unit ( CFU ) counts per gram for coliform in faeces varied from 2 . 6-6 . 4 X 107 and 1 . 8-2 . 7 X 108 for the pigs and form workers tested respectively . Random identification of 291 colonies on MacConkey agar on the basis of frequency of occurrence of numbers of lactose and nonlactose fermenters yielded 94 . 2 % Escherichia coli (E.coli).The other genera isolated includes Enterobacter , Klebsiella , Edwarsiella , Citrobacter and Serratia . About 8.2 % and 29.6 % of the E. coli isolates were non-lactose fermenters on MacConkey agar and did not show the characteristic green metallic sheen on Eosin- Methylene Blue agar respectively.